1991
DOI: 10.1111/j.1574-6968.1991.tb04207.x
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of entericCampylobacterby human and murine granulocytes

Abstract: Summary The phagocytosis of enteric Campylobacter strains by murine and human granulocytes was studied in vitro. The number of fluorescein isothiocyanate‐labelled bacteria per granulocyte was determined microscopically. The phagocytic index is strain‐dependent, ranging from 0.05 to 0.4 bacteria per granulocyte. Human granulocytes phagocytose Campylobacter sp. with a twofold higher effectivity than murine cell. Opsonization with immune sera increased phagocytosis 11.6‐fold; flagella‐defective mutants were phago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Furthermore we showed that although neutrophils respond towards C. concisus without these being opsonised with serum the response is increased when bacteria are opsonised. Previous studies have found that opsonised C. jejuni generates a higher degree of neutrophil granulocyte response than non-opsonised bacteria [1,2,15] correlating well with our findings. Our study design does not allow us to definitely conclude whether opsonisation induces increased phagocytosis of C. concisus .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore we showed that although neutrophils respond towards C. concisus without these being opsonised with serum the response is increased when bacteria are opsonised. Previous studies have found that opsonised C. jejuni generates a higher degree of neutrophil granulocyte response than non-opsonised bacteria [1,2,15] correlating well with our findings. Our study design does not allow us to definitely conclude whether opsonisation induces increased phagocytosis of C. concisus .…”
Section: Discussionsupporting
confidence: 92%
“…Our study design does not allow us to definitely conclude whether opsonisation induces increased phagocytosis of C. concisus . Previous investigations of C. jejuni and H. pylori [2-4] have shown that opsonisation significantly increases phagocytosis in both complement-dependent and –independent assays. Combination of heat-treated and untreated serum produced a higher opsonic activity for C. jejuni stimulation of neutrophils [4].…”
Section: Discussionmentioning
confidence: 99%